PENGARUH TEKNIK RELAKSASI NAFAS DALAM TERHADAP PENURUNAN NYERI POST-OPERATIF PADA PASIEN FRAKTUR: A LITERATURE REVIEW - Sridarmayanti, Ni Made; Raya, Nyoman Agus Jagat (Coping: Community of Publishing in Nursing; Vol 11 No 3 (2023): Juni 2023DO - 10.24843/coping.2023.v11.i03.p08, 2023)
Fracture becomes a musculoskeletal problem caused primarily by a traumatic injury to the bone. Fractures cause patients to experience pain both before and after surgery. Giving non-pharmacological therapy in fracture patient like deep breathing exercises aim to optimize nursing care to reduce pain and improve comfort. The purpose of this study is to review the literature on deep breathing exercises for reducing post-operative pain in fracture patients. The research design was a literature review made from Google Scholar dan ScienceDirect. The inclusion criteria used were fracture patients; experimental research designs; research articles discussing fractures, deep breathing exercises, and pain; use of Indonesian or English; accessible full-text; and the year of publication 2018-2022. The process of searching and selecting articles uses the prism flow diagram systematic literature review method which will then be categorized based on levels of evidence. Based on the analysis of research articles using the JBI Critical Appraisal Tools, it was found that deep breathing exercises can help reduce post-operative pain in fracture patients. One journal combined deep breathing exercises and range of motion, two articles combined music therapy, and three articles focused solely on deep breathing exercises. The literature had one level of evidence, namely Level 2. Four articles were quasi-experimental studies (2.c) and three articles were pre-experimental studies (2.d). The study concluded that deep breathing exercise is one of the non-pharmacological therapies that can help reduce post-operative pain in fracture patients. This study is expected to add to the literature by providing nursing interventions to reduce post-operative pain in fracture patients.